On Wheels : Five Easy Pieces - Holroyd, Michael (London Chatto & Windus, 2012)
Learning to drive was no easy matter for the author: the lessons required military precision when practising how to get in and out of his car correctly. Weaving together memoir and historical anecdote, this title traces his relationship with cars through a lifetime of biography.
Keywords: Automobile Driving -- Automobiles -- Automobiles